Suzuki–Miyaura Coupling of Aryl Chlorides with Arylboronic Acids Using the Morpholine–NiCl2 Catalyst System. Issue 31 (16th September 2014) - Abe, Taichi; Mino, Takashi; Watanabe, Kohei; Sakamoto, Masami
Abstract: We report a new catalyst system, morpholine–NiCl2, for the Suzuki–Miyaura coupling of aryl chlorides with aryl‐ or alkenylboronic acids to give biaryl compounds. This catalyst system is easy to apply on a large scale because of its easy preparation and the use of inexpensive reagents. In addition, analysis of the residual nickel shows only 9.7 ppm remaining after normal work‐up. This catalyst system has been applied to 26 compounds to give a variety of biaryl products, including hetero‐biaryl compounds. Abstract : We report morpholine–NiCl2 as a new catalyst system for the Suzuki–Miyaura coupling of aryl chlorides with aryl‐ or alkenylboronic acids to give biaryl compounds. This catalyst system is easy to apply on a large scale because of its easy preparation and the use of inexpensive reagents, and has broad substrate scope. Analysis of the residual nickel showed only 9.7 ppm remaining after work‐up.